1985
DOI: 10.1172/jci112063
|View full text |Cite
|
Sign up to set email alerts
|

Terbutaline-induced desensitization of human lymphocyte beta 2-adrenoceptors. Accelerated restoration of beta-adrenoceptor responsiveness by prednisone and ketotifen.

Abstract: We investigated, in 36 healthy volunteers, the effects of prednisone and ketotifen on recovery of lymphocyte j2-adrenoceptor density (determined by (-)-'"iodocyanopindolol binding) and responsiveness (assessed by lymphocyte cyclic AMP IcAMPI responses to 10 AtM (-)-isoprenaline) after desensitization by the p2-agonist terbutaline. Terbutaline (3 X 5 mg/d) decreased lymphocyte #2-adrenoceptor density by -40-50%; concomitantly, lymphocyte cAMP responses to 10 ,gM (-)-isoprenaline were significantly reduced. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(61 citation statements)
references
References 39 publications
8
52
0
1
Order By: Relevance
“…We and others have shown in several studies that, in humans, chronic oral treatment with the ␤ 2 AR agonist terbutaline causes desensitization of ␤ 2 AR-mediated effects (3,5,7,(14)(15)(16). Very recently, we found that, in contrast to in vitro observations (11), the extent of terbutaline-induced desensitization of cardiac ␤ 2 AR responses after a 2-wk oral treatment with 3 ϫ 5 mg/day terbutaline was not different in volunteers carrying the Gly16Gly or Glu27Glu allele; however, volunteers homozygous Glu27Glu exhibited a delayed onset in desensitization (7).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We and others have shown in several studies that, in humans, chronic oral treatment with the ␤ 2 AR agonist terbutaline causes desensitization of ␤ 2 AR-mediated effects (3,5,7,(14)(15)(16). Very recently, we found that, in contrast to in vitro observations (11), the extent of terbutaline-induced desensitization of cardiac ␤ 2 AR responses after a 2-wk oral treatment with 3 ϫ 5 mg/day terbutaline was not different in volunteers carrying the Gly16Gly or Glu27Glu allele; however, volunteers homozygous Glu27Glu exhibited a delayed onset in desensitization (7).…”
Section: Discussionmentioning
confidence: 94%
“…To answer this question, in the present study, we assessed in 6 healthy volunteers heterozygous for Thr164Ile ␤ 2 AR polymorphism and in 10 volunteers homozygous WT ␤ 2 AR terbutaline infusion induced increase in heart rate (HR) and shortening of the HR-corrected duration of the electromechanical systole [QS 2 c; an established measure of contractility (2)] before and after 2-wk treatment with 3 ϫ 5 mg/day terbutaline, a protocol that has been shown to evoke desensitization of ␤ 2 AR responses in vivo (3,5,7,16).…”
mentioning
confidence: 99%
“…The steroid had no effect on receptors that had not been down-regulated. A single dose of 100 mg oral prednisolone produced similar up-regulation, within 8 to 10 h of receiving Review 115 the drug [56]. The mechanism of this effect is not yet fully understood, but it may involve an increase in the rate of de novo synthesis of receptors or, a reversal or inhibition of internalisation of receptors from the cell surface.…”
Section: The Influence Of Disease Modifying Therapymentioning
confidence: 95%
“…Ketotifen has been shown both to accelerate upregulation of previously down-regulated lymphocyte 2-receptors, and to attenuate down-regulation. This has been found to correlate with an attenuation of the tolerance to systemic, and airway f2-mediated effects in normal subjects [56,64]. Ketotifen has also been shown to up-regulate lymphocyte P2-receptors in asthmatics, a change associated with an improvement in pre-bronchodilator peak flows but no change in reversibility [59].…”
Section: The Influence Of Disease Modifying Therapymentioning
confidence: 96%
“…many pro-inflammatory and immune cells, including mast cells [35], macrophages [36], neutrophils [37], lymphocytes [38], eosinophils [39], epithelial and endothelial cells [40,41], and both type I and type II alveolar cells [10,42,43]. Thus, many cell types within the lung that are implicated in the pathogenesis of asthma are potential targets of inhaled b 2 -adrenoceptor agonists.…”
Section: Adrenoceptors In the Lungmentioning
confidence: 99%